DYNAMICS OF IMPLEMENTATION AND ENFORCEMENT OF CODE OF ETHICS AND GUIDELINES FOR JUDGES' CONDUCT FOR MILITARY JUDGES - PARLUHUTAN SAGALA; IRMAN PUTRA; ARIEF FAHMI LUBIS (CV KULTURA DIGITAL MEDIA, 2024)
It is reasonable to expect good judges to render decisions that uphold the law and demonstrate a sense of justice. The purpose of this study is to demonstrate how, if the Code of Ethics for Guidelines for Judges' Conduct (KEPPH) is followed in carrying out these responsibilities and in other contexts, both directly and indirectly, the perceptions and expectations of justice seekers will ultimately change. restored in the realization of military justice. noble, not cloudy, and free from sinful beliefs and actions. In qualitative research, data were collected methodically, factually, and quickly using descriptive methodology in accordance with the description at the time of the study. The findings of this study indicate that openness, participation, accountability, placing the right person in the right place, and objectivity must be prioritized in the recruitment and selection process to produce competent Military Judges. Although the recruitment and selection process has succeeded in producing Military Judges who uphold the principles of KEPPH and become God's representatives on earth, Military Judges are also human beings and therefore prone to error. Therefore, they require continuous education and training.